Establishment of Pathogen-Free Rhipicephalus bursa Colonies Under Laboratory Conditions for the Vector Competence Studies - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Mdpi, 2025)
Rhipicephalus bursa, the primary vector of Babesia ovis, is also considered to transmit Theileria, Babesia, and Anaplasma spp. These claims are based on pathogen detections rather than experimental validation. To confirm vector competence, sterile ticks must acquire pathogens from infected hosts and transmit them to other hosts. The basic step is establishing a pathogen-free tick colony. In this study, engorged R. bursa females were collected from 12 infested livestock and allowed to lay eggs. The carcasses and larvae were screened for tick-borne pathogens using nPCR. The 0.150 g pathogen-free F1 larvae were fed on New Zealand rabbits, resulting in 592 engorged nymphs that molted into F1 adults. Eighty F1 adults were fed on pathogen-free splenectomized sheep, producing the next larval generation (F2). This protocol was repeated to produce F3 larvae. At the end of all developmental stages, ticks were screened via nPCR and found to be negative for tick-borne pathogens. The sheep were monitored for 63 days with no clinical signs or positive nPCR results, confirming F3 larvae as pathogen-free and suitable for vector competence studies. The R. bursa life cycle was completed in 72-153 days, providing a reliable model for vector competence research and offering valuable insights into its biological parameters.
Keywords: Rhipicephalus bursa; tick colony; tick-borne pathogen-free; vector competence study